Multi-level state interventions and gender equality in higher education institutions: The Irish case - Pat O'Connor; Gemma Irvine (Administrative Sciences, 2020)
Much of the work on gender equality in higher educational institutions (HEIs) has concentrated on the organizational level. The original contribution of this article lies in its focus on state policy developments and interventions. We focus on Ireland as a specific national context, highlighting multi-level state interventions and looking at their impact on HEIs. Using secondary data analysis (including documentary analysis) and focusing particularly on the period since 2014, state initiatives to tackle the problem of gender inequality from various angles are outlined. They include the introduction of Athena SWAN; the Expert Group Review; the Gender Equality Taskforce; the Senior Academic Leadership Initiative; research funding agency initiatives and those around sexual harassment. In evaluating their impact, we look at the gender pay gap, the gender profile of the professoriate and senior management as well as other indicators of cultural change in HEIs. The article concludes that the best possibility of leveraging change arises when it is driven at the state (macro); the HEI (meso) and the situational (micro) level simultaneously, by gender competent leaders willing to tackle the historically male dominated, masculinist criteria, procedures, processes and micropolitical practices that are 'normalized' in HEIs.
Keywords: 350; state; gender equality; higher educational institutions; intervention ns; multi-level; genderpay gap; gender parity; Irish; professoriate; Athena SWAN